Rhetorical ethos: between téchne rhetoriké and practical disciplines - Mathiesen, Aleksandra (Hybris, 2015)
Inquiring Aristotelian conception of rhetoric as an art of persuasion, the author of the article aims in presenting rhetorical ethos and rhetoric itself in reference to practical disciplines, politics and ethics. Understanding rhetoric’s autonomy as a theoretical postulate this inquiries introduce a demand of functionality and axiological awareness: to treat art of rhetoric as an organon for the practical disciplines and to acquire attention of normative problems concerning particular features of rhetoric and rhetorical ethos. The article investigates Aristotle’s original conception of rhetoric and the troubled but essential connection between techne and praxis. Proposing a solution, the author initially puts forward a project of establishing a new normative conception of rhetorical ethos meeting the demands of contemporary praxis (especially in the field of education) on the basis of a concept of uprightness.